Historical dictionary of Costa Rica - Díaz Arias, David; Viales Hurtado, Ronny José; Marín Hernández, Juan José (Historical dictionaries of the Americas., 2019)
"Historical Dictionary of Costa Rica contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture."--Provided by publisher